Studies on the Constituents of Shells and Peduncles of Different Eco-races of Antheraea mylitta D - Goel, R. K.; Sinha, A. K.; Brahmachari, B. N.; Sengupta, K. (Indian Forester, 1987)
Shells and peduncles of nine eco-races viz., Raily, Daba TV, BOgal, Moonga, Modia, I.aria. Bhandara, Mandla and Jadai of Antheraea mylitta D. were analysed for the four constituents viz moisture, total nitrogen, total minerals and boil off loss. Results of analyses of variance reveal that the eco-race; differ significantly from each other in respect of all the four constituents of shells and peduncles. Considering inter-racial variations, mean values for all the constituents except boil off loss are higher in cocoon shells. Total nitrogen varies from 19.34% (Moonga) to 16.78% (Jadai) in cocoon shell. And from 17.82% (Railey) to 16.06% (I aria) In peduncles while total minerals content ranges between 6.00% (Raily) and 2.27% (Mandla) for shells and between 3.85% (Bhandara) and 0.823% (Raily) for peduncles. Similarly, boil of loss content varies from 21.15% (Bhandara) and 10.38% (Daba TV) in shells and from 36.01% (Raily) to 23.54% (Mandla) in peduncles. Cocoon shells and peduncles of Mandla eco-race have the hiehest moisture content (12.80% and 11.43%) and that of Raily eco-race the lowest (5.01% and 4.63%) respectively.